2017
DOI: 10.1002/ajim.22766
|View full text |Cite
|
Sign up to set email alerts
|

Occupational styrene exposure and acquired dyschromatopsia: A systematic review and meta‐analysis

Abstract: Background Styrene is a chemical used in the manufacture of plastic-based products worldwide. We systematically reviewed eligible studies of occupational styrene-induced dyschromatopsia, qualitatively synthesizing their findings and estimating the exposure effect through meta-analysis. Methods PubMed, EMBASE, and Web of Science databases were queried for eligible studies. Using a random effects model, we compared measures of dyschromatopsia between exposed and non-exposed workers to calculate the standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 62 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…However, the analysis was not designed to yield a threshold concentration or NOAEC, and the authors reported no consensus regarding a threshold exposure concentration that causes acquired dyschromatopsia. Of the 15 studies evaluated qualitatively by Choi et al (2017), only that reported by Seeber, Bruckner, and Triebig (2009b) did not support the hypothesis. Of possible relevance in this regard is the fact that Seeber, Bruckner, and Triebig (2009b) excluded participants on the basis of demonstrated red-green deficiency (as well as "congenital color-blindness") in order to avoid potential impacts of this predominantly inherited deficiency on the color discrimination test that could have "inflated" styrene impacts in other studies.…”
Section: Non-cancer Health Effectsmentioning
confidence: 88%
See 3 more Smart Citations
“…However, the analysis was not designed to yield a threshold concentration or NOAEC, and the authors reported no consensus regarding a threshold exposure concentration that causes acquired dyschromatopsia. Of the 15 studies evaluated qualitatively by Choi et al (2017), only that reported by Seeber, Bruckner, and Triebig (2009b) did not support the hypothesis. Of possible relevance in this regard is the fact that Seeber, Bruckner, and Triebig (2009b) excluded participants on the basis of demonstrated red-green deficiency (as well as "congenital color-blindness") in order to avoid potential impacts of this predominantly inherited deficiency on the color discrimination test that could have "inflated" styrene impacts in other studies.…”
Section: Non-cancer Health Effectsmentioning
confidence: 88%
“…A "mild" publication bias against smaller studies with negative results was suggested, but implications were not discussed. Choi et al (2017) concluded that available evidence supports the hypothesis that chronic occupational exposure to styrene at "levels below most regulatory agency-prescribed exposure limits" can induce subclinical deficits in color vision. However, the analysis was not designed to yield a threshold concentration or a No-Observed-Adverse-Effect-Concentration (NOAEC), and the authors reported no consensus regarding a threshold exposure concentration that causes acquired dyschromatopsia.…”
Section: Non-cancer Health Effectsmentioning
confidence: 88%
See 2 more Smart Citations
“…Occupational exposure to solvents or some other chemicals, such as organophosphate pesticides, may lead to color vision loss that is usually subclinical, and thereby vision testing may be favorable in the evaluation of early neurotoxicity of chemicals in exposed workers [ 129 ]. The impairment of color discrimination was notified in cases of exposure to environmental levels lower than the occupational limits proposed [ 130 ].…”
Section: Optic Neuropathy Induced By Toxic Substancesmentioning
confidence: 99%